Penerapan double slope solar still (DSSS) sebagai solusi permasalahan air bersih di Desa Semedo Kecamatan Kedungbanteng Kabupaten Tegal - Irfan Santosa; Galuh Renggani Wilis; Noor Zuhry (Cv. Utility Project Solution, 2022)
Semedo Village, Kedungbanteng District, Tegal Regency is located in the northwest part of Central Java Province with a geographical location of 108°57'6”-109°21'30” east longitude and 6°02'41”-7°15'30” latitude which has an area of approximately 878.89 km2. The village has problems with springs where the water content contains high NaCl (salt) and cyanide elements reach 0.2%. So the solution to overcome this problem is to apply a double slope solar still (DSSS) distillation device through the PkM program. The implementation method is carried out with hard programs and soft programs. Hard programs are programs that can be seen in real form, namely making and applying DSSS tools and soft programs including outreach activities to the community. The results of this PkM activity are the DSSS model distillation device and socialization to the community regarding how the distillation tool works and the quality of the distilled water that has gone through a laboratory testing process where distilled water is suitable for consumption but there must be a cooking process first and the quality of salt that is not fit for consumption